Increasing Student Creativity and Collaboration in Biochemistry Practicum through the Application of Project Based Learning Model - Firdiawan Ekaputra (PT ARRUS Intelektual Indonesia, 2024)
Finding out how well project-based learning works in biochemistry practicum courses to foster student creativity and teamwork was the aim of this study. One research sample class and a pre-experiment design were employed in this investigation. The samples used in this study were Jambi University Chemistry Education Study Program students who took the Biochemistry Practicum course, class R-002, during the 2023–2024 academic year. Questionnaire tools were employed in this study to gather data on teamwork and creativity. The difference in student creativity and collaboration data before and after the application of the project-based learning model was then tested for normality to determine the distribution of data for each variable and paired sample t-test to determine the effectiveness of the application of the project-based learning model. The significance results based on the paired sample t-test showed 0.000 for the creativity variable and 0.003 for the student collaboration variable. Based on these results, it can be concluded that the application of the project-based learning model in biochemistry practicum courses is effective in increasing student creativity and collaboration.